Testing and Diversity in Postsecondary Education: The Case of California - Daniel Koretz (Arizona State University, 2002)
The past several years have seen numerous efforts to scale back or eliminate affirmative action in postsecondary admissions. In response, policymakers and postsecondary institutions in many states are searching for ways to maintain the diversity of student populations without resorting to a prohibited focus on race. In response to these changes, this study used data from California and a simplified model of the University of California admissions process to explore how various approaches to admissions affect the diversity of the admitted student population. "Race-neutral" admissions based solely on test scores and grades were compared with the results of actual admissions before and after the elimination of affirmative action. A final set of analyses explored the effects on diversity of alternative approaches that take into account factors other than grades and scores, but not race or ethnicity. Replacing the former admissions process that included preferences with a race-neutral model based solely on GPA and SAT-I scores substantially reduced minority representation at the two most selective UC campuses but had much smaller effects at the other six, less selective campuses. SAT-I scores contributed to but were not the sole cause of the underrepresentation of African American and Hispanic students. A race-neutral model based solely on GPA also produced an underrepresentation of minorities, albeit a less severe one. None of the alternative admissions models analyzed could replicate the composition of the student population that was in place before the termination of affirmative action in California. The only approach that substantially increased the representation of minority students was accepting most students on the basis of within-school rather than statewide rankings, and this approach caused a sizable drop in both the average SAT scores and the average GPA of admitted applicants, particularly among African American and Hispanic students. Although admissions systems differ, the basic findings of this study are likely to apply at a general level to many universities and underscore the difficulty of providing proportional representation for underserved minority students at highly selective institutions without explicit preferences.